2005
DOI: 10.1016/j.ultrasmedbio.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of ultrasound elasticity imaging to direct mechanical measurement in aging DVT in rats

Abstract: Previous ultrasound elasticity imaging experiments supported a generally accepted concept that the hardness of deep venous thrombi increases with thrombus aging. Results also showed that this noninvasive imaging technique can accurately predict thrombus age through strain estimates in a well controlled animal study. In the present study, as an alternative means to characterize elastic properties of thrombi, we employed a direct mechanical measurement system to estimate Young's modulus of ex vivo thrombi. Unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 19 publications
4
70
0
Order By: Relevance
“…If the clot is acute, the patient should be given intravenous heparin to disperse it, followed by oral anticoagulant; but if the clot is chronic, only oral anticoagulant should be prescribed. Using a rat model, good correlation has been demonstrated between the age-related Young's modulus of thrombus determined by ultrasonic elastography and that subsequently directly measured ex vivo [28]. This suggests that ultrasonic thrombus elastography might be used to select the appropriate therapy for patients with deep vein thrombosis.…”
mentioning
confidence: 82%
“…If the clot is acute, the patient should be given intravenous heparin to disperse it, followed by oral anticoagulant; but if the clot is chronic, only oral anticoagulant should be prescribed. Using a rat model, good correlation has been demonstrated between the age-related Young's modulus of thrombus determined by ultrasonic elastography and that subsequently directly measured ex vivo [28]. This suggests that ultrasonic thrombus elastography might be used to select the appropriate therapy for patients with deep vein thrombosis.…”
mentioning
confidence: 82%
“…The expression for displacement can be simplified to , where C is a coefficient of proportionality. Since the gradients are applied in one direction at a time the coefficient of proportionality in the i th direction is (2) where G o,i is the gradient amplitude in the i th direction.…”
Section: Theory Mre Principlesmentioning
confidence: 99%
“…Changes in material stiffness can indicate the presence of tumors and other diseases [1]. In the case of deep venous thrombosis (DVT), hardness of the thrombus is closely related to thrombus maturity, which in turn determines the appropriate course of treatment [2]. Physicians have long relied on hand palpation to detect the presence of a tumor where other imaging methods such as ultrasound, CT, and MRI have failed to do so.…”
Section: Introductionmentioning
confidence: 99%
“…A large strain formulation was used with the rubber/foam material model, named as Sussman-Bathe (Sussman and Bathe, 2009). In this paper, measured stress-strain curve obtained from ultrasound elasticity imaging of a 3-day-old thrombus (Xie et al, 2005) was set precisely to the Sussman-Bathe model as it is shown in Fig. 2.…”
Section: Blood and Clot Materials Propertiesmentioning
confidence: 99%